Phylogenetic characterization of a microsporidium (Nosema sp.) isolated from the mulberry pest, Hemerophila atrilineata - Guan, Rui; Shen, Zhongyuan; Zhu, Feng; Chen, Darui; Zhang, Jiao; Hou, Jiange; Dong, Shinan; Tang, Xudong; Xu, Li (Folia parasitologica, 2012)
Microsporidia are a group of obligate intracellular unicellular eukaryotes that can parasitize a wide variety of other eukaryotes ranging from protists to invertebrates and vertebrates. In this study, we examined the microsporidium Nosema sp. isolated from the mulberry pest, Hemerophila atrilineata Butler, 1881, named herein "Nosema sp. HA". The fresh spores were long oval in shape, 3.8 +/- 0.4 microm in length and 1.9 +/- 0.3 microm in width. Analysis of tissue infection of silkworm, Bombyx mori Linnaeus, 1758, indicated that the midgut, Malpighian tubules, muscle, fat body, silk glands, hemocytes, nerve tissue and gonads of silkworm were infected with Nosema sp. HA. The complete rRNA gene sequence of this microsporidium contained 4 305 base pairs (GenBank Accession JN882299), including the large subunit rRNA (2492 bp), the internal transcribed spacer (187 bp), the small subunit rRNA (1232 bp), the intergenic spacer (279 bp) and the 5S region (115 bp). The organization of the rRNA gene is 5'-LSU-ITS-SSU-IGS-5S-3'. Phylogenetic analysis, comparison of sequence identities and the arrangement in the rRNA gene subunits suggested that this isolate is separate from other Nosema species.
Keywords: fungální RNA; Animals; Microsporidia; RNA, Ribosomal; interakce hostitele a parazita; můry; zvířata; fylogeneze; Host-Parasite Interactions; RNA, Fungal; Phylogeny; Moths; RNA ribozomální